OFFENSES AGAINST LIFE AND BODILY INTEGRITY COMMITTED AS RESULT OF DRIVING A VEHICLE WITHOUT A DRIVING LICENSE OR UNDER THE INFLUENCE OF ALCOHOL OR OTHER SUBSTANCES, OR BY EXCEEDING THE SPEED LIMIT: INDIRECT INTENT OR RECKLESSNESS? - Andreea-Mihaela STANCU (Challenges of the Knowledge Society)
Nowadays, driving a vehicle without a driving license, by exceeding speed limits or being under the influence of alcohol or other substances, seems to become a routine. More and more drivers use alcohol or psychoactive substances before getting behind the wheel. More and more people are losing their lives as a result of these facts. How can this situation be improved, since most of the time, driving a vehicle on public roads without a driving license, by exceeding the speed limits, or being under the influence of alcohol or other substances ends tragically, resulting in the death of other people participating in traffic. I can say such a situation is equivalent to ruined lives, not only regarding the injured victim, but also, regarding the defendant, too. The determination of the subjective side of the offenses resulting in death or personal injury of a person in the above-mentioned contexts divided legal specialists into two camps: those who think it is talked about indirect intent and those who think it is talked about recklessness. This paper aims to analyse what is the correct legal classification in such situations, starting from the current legal regulations and the analysis of some concrete examples from the judicial practice, emphasising the aspects meant to influence the retention of the form of guilt of the indirect intent, respectively of the recklessness.